Rainfall and temperature influence expression of foliar symptoms of grapevine leaf stripe disease (esca complex) in vineyards - CALZARANO, Francesco; OSTI, Fabio; BARÁNEK, Miroslav; DI MARCO, Stefano (Phytopathologia Mediterranea, 2018)
Two vineyards in the Abruzzo Region, central Italy, affected by grapevine leaf stripe disease (GLSD), were monitored for incidence and severity of foliar symptoms of the disease for 21 consecutive years (1994 to 2014). Each year, rainfall and temperature were recorded. Correlations between symptom incidence or severity and rainfall or temperature of different periods of the year or single months were assessed. July rainfall and temperature were highly correlated with incidence and severity of leaf symptoms. The vineyards were characterized by high longevity, vigour and yields, and a particular dynamic of GLSD. In the period following 2005, the year of peak vine mortality, there was a decrease of the expression of foliar symptoms, which was not correlated with both of the climate parameters. Greater mortality occurred for vines showing severe symptoms at the first appearance of GLSD than for vines with low severity.